ABOUT THE RELATIONSHIP BETWEEN EDUCATION AND DEVELOPMENT OF THE PSYCHE IN ADOLESCENCE - Anjos, Ricardo Eleuterio dos; Ponce, Rosiane de Fatima [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
Based on the assumptions of cultural-historical psychology and critical-historical pedagogy, this article focuses on the relationship between education and development of the psyche in adolescence. It conceptualizes human psyche as a subjective reflection of objective reality formed from a complex functional system consisting of psychological cognitive-affective functions. It postulates that the subjective image of reality is organized from thinking by concepts, which is the highest form of conceptual thinking what is reached only in adolescence. This way of thinking is presented dialectically as a result and condition of appropriation of non-daily objectivations of mankind, like art, philosophy, and science. Hence the article considers the important role of school education which, in its specificity, transmits in a direct and intentional way the classical know ledge to students.
Keywords: School education; Psychic development; Adolescence